A Spaniard in Aguinaldo's Army: the military journal of Telesforo Carrasco y Perez - Carrasco y Perez, Telesforro (Mandaluyong, MM : Solar Pub, 1986)
With the original Spanish text
Keywords: Carrasco y Perez, Telesforo, 1873-1916; Philippines -- History -- Revolution, 1896-1898 -- Personal narratives, spanish; philippines -- History -- Revolution, 1899-1901 -- Personal narratives, Spanish